A Produção do Flagelo : a re-produção do espaço social da seca na cidade de Mossoró (1877-1903-1915) - Maciel, Francisco Ramon de Matos (2013)
The great droughts re- produced spaces in the city of Mossoró / RN in the end of the nineteenth century to the beginning of the twentieth century. Its dimension exceeds the climatic effects becoming social locus when advances over the political and economic sectors, social and cultural of the North / Northeast Brazilian societies during that period. This way, analyzing the re-production of social space in episodes of Mossoró‟s droughts is our toil. So try to reveal each segment, route and aspect of production of space in its size and interface between the perceived, conceived and lived, and subjects related to it - refugees, population and authorities - during the droughts of 1877, 1903 and 1915 within Mossoró city. Therefore, issues such as the constitution and representation of the city and social space in the terrifying experience of the drought of 1877, the production of fixed objects and flows of the urban web through of migrant labor, attempts to control, discipline and spatial planning and ways to resistance to these charges in daily sphere are key issues addressed in this work. For this we use diverse sources as minutes of the city council, reports from provincial presidents, media, memory books and others that sustain us in building our narrative and problematic. This way, the spatial production of Mossoró‟s droughts reveals itself in the field of relations and political-economic transformations and sociocultural, inextricably, that shapes and mobilizes your own social space